Biochemical and Microbiological Aspects of the Oral Cavity of Children and Young People with Neurological Impairment and Oropharyngeal Dysphagia - Duarte, Janaina Costa Marangon; Costa, Isabela Bazzo; Teixeira, Daniel de Bortoli; Fregatto, Luiz Fernando; Mendes, Claudemir Gregorio; Mascarin, Aline Maria Noli; da Silveira Junior, Salum Bueno; Serva, Bianca Eduarda Baptistella Mesquita; Comar, Livia Picchi; da Silva, Roberta Gonçalves [UNESP]; Buchaim, Daniela Vieira; Buchaim, Rogerio Leone; et al. (MDPI, 2023)
The components and the salivary flow have a direct influence on the composition of the oral microbiota of children and young people with oropharyngeal dysphagia, and studies have already demonstrated the excessive accumulation of supragingival dental calculus in individuals with enteral nutrition. This study aimed to compare the oral hygiene, biochemical, and microbiological aspects of the oral cavity of children and young people with neurological impairment and oropharyngeal dysphagia. Forty children and young people with neurological impairment and oropharyngeal dysphagia were enrolled and divided into two groups: group I, encompassing 20 participants fed via gastrostomy; and group II, encompassing 20 participants fed via the oral route. Oral hygiene and salivary pH and flow were assessed, and a polymerase chain reaction was performed to evaluate the messenger RNA expressions of Porphyromonas gingivalis, Tanerella forsythia, and Treponema denticola. In groups I and II, the mean Oral Hygiene Index—Simplified scores were 4 and 2, respectively, showing a significant difference; the mean Calculus Index scores were 2 and 0, respectively, showing a significant difference; and the mean pH was 7.5 and 6.0, respectively, showing a significant difference. Bacterial analysis indicated no association between the two groups. It can be concluded that children and young people who use gastrostomy had a poorer oral hygiene, greater dental calculus deposition, and higher salivary pH. The saliva of patients in both groups contained Porphyromonas gingivalis, Tanerella forsythia, and Treponema denticola.
Keywords: deglutition disorder; dental calculus; dysphagia; neurological disorders; oral hygiene; saliva